Are mild cleansers appropriate for hand hygiene in the COVID era? An in vitro investigation of the antiviral efficacy of different hand hygiene products - Winder, Natalie; Ashraf, Zahra; Gohar, Sara; Baalbaki, Nada; Cork, Micheal; Danby, Simon; Muthana, Munitta (Frontiers in Virology, 2023)
1 Background: Washing hands with soap and lukewarm water for 20 seconds is a fundamental measure advocated worldwide to help control the spread of viral disease. However, these practices can induce irritant contact dermatitis, particularly in healthcare professionals (HCP). HCP typically manage their condition by substituting soap with cleansers containing mild surfactants and/or emollient ingredients (skin friendly cleansers) to mitigate skin damage and/or using topical emollients afterwards for repair. Despite this widespread practice there is very limited evidence supporting the efficacy of these interventions in the prevention of viral propagation. Methodology: Human coronavirus [HCoV], herpes Simplex virus [HSV]-1, influenza [IVA], adenovirus [Ad] and Murine Norovirus [MNV] were used in this study. In vitro analysis using plaque assays and tissue culture infectious dose 50 (TCI50) were used to assess virus viability after incubation with test products (soaps and skin friendly cleansers), over a range of concentrations and time points. Transmission electron microscopy (TEM) was used to determine virus architecture and size and viral replication genes were measured by RT-PCR. Results/conclusions: Enveloped viruses demonstrated greater susceptibility over a range of test products suggesting some skin friendly cleansers (SFCs) are a suitable alternative to soap (envelope depending). However, no virucidal activity was observed for non-enveloped viruses. Water type (soft/hard) and pre-exposed hand hygiene conditions (clean/dirty) made little difference to the effectiveness of both soaps and SFCs. Therefore, new hand hygiene regimes should be implemented on a virus-virus basis, with specific emphasis on the presence or absence of a viral envelope.